Messianic Nihilism and Allegory. Benjamin between Schmitt and Taubes - Gurisatti, Giovanni (Scenari, 2021)
Inside of the correspondence between Jacob Taubes and Carl Schmitt (Adelphi 2018) Benjamin’s character and work play a fundamental role in the theological-political interpretation that Taubes is giving of it. In his writings, aiming to promote the “scandalous” relationship between Schmitt and Benjamin, Taubes moved with intellectual courage, but his strategy was not safe from vices and presented shoves and gaps. In order to clarify these aspects it’s useful to retrace the relationship that, in Benjamin, intertwines theology and aesthetics, focused on the mystic-apocalyptic idea of “Messianic Nihilism”, that lays at the basis not only of the peculiar political inspiration of his work, but also of his conception of art and history.